The employment relationship: a comparative overview (Geneva, 2011)
"Changes in the world of work have modified traditional notions of the employment relationship. These changes shape the scope of protection and application of labor legislation and automatically affect the way labor law is implemented. The Employment Relationship provides cross-national analysis of this important phenomenon.